Material Dependent Influence of Ring/Spot Beam Profiles in Laser Powder Bed Fusion - Chechik, Lev; Schwarzkopf, Karen; Rothfelder, Richard; Grünewald, Jonas; Schmidt, Michael (Additive Manufacturing Letters, 2024)
In recent years, the topic of beam shaping for improved laser material processing has rapidly grown influencing metal laser powder bed fusion (PBF-LB/M). Given the need to reduce the cost and improve control of the PBF-LB/M process to make it more competitive with traditional manufacturing methods, increasing productivity of PBF-LB/M is critical. When research reports a new beam profile (e.g. ring profile) to improve productivity on a specific material, it is often generalised, and assumed to have the capability to improve productivity in PBF-LB/M across the board. In this work, we use both low-fidelity simulations and experimental work to investigate the difference between Gaussian and ring/spot beam profiles on metals with very different thermal properties (a stainless steel and an aluminium alloy). We show that the two materials have opposite responses to the change in beam profile (both in terms of melt pool dimensions and thermal gradients); further, the most beneficial intensity distribution is dependent on the energy input to the material. This exemplifies yet another way in which the PBF-LB/M process is non-linear and contradicts the idea that a ring/spot laser profile is beneficial for all laser processing technologies. This highlights the need for further research into the non-linear effect of varying intensity distributions on laser processing before the benefits of dynamic beam shaping can be truly realised.<br
Keywords: Beam shaping; Additive manufacturing; Laser material processing